The Effects of Sex-Type, the Sex of the Avatar, and Salience of the Sex of the Avatar on Emotional Valence and Arousal - Prettyman, Duncan V.; Bolls, Paul D. (Frontiers in Psychology, 2021)
The objective of this study was to investigate the effects of avatar sex, salience of avatar sex, and player sex-type on less conscious embodied emotional arousal and valence vs. consciously perceived emotional arousal and valence elicited by a gaming experience. The experiment conducted a 2 avatar sex (female × male) × 2 salience of avatar sex (high × low) × 2 player sex-type (sex-typed × non-sex-typed) mixed model factorial design. Participants were randomly assigned to one of two gameplay conditions (high-salience male and female avatar or low-salience male and female avatar) and then played two 15-min sessions of a video game—one session playing the game as a male avatar and one session playing the game as a female avatar. The order in which participants played as either a male or female avatar was randomized. Psychophysiological indicators of arousal (skin conductance) and valence (facial electromyography) were recorded during gameplay. Self-report measures of arousal and valence were obtained immediately after each 15-min session of gameplay. Data analysis tested hypotheses concerning the effects of avatar sex, salience of avatar sex, and player sex-type separately on real-time embodied variation in arousal and valence as revealed through physiological indicators and conscious perception of arousal and valence obtained through self-report measures.